Knowledge architecture for the wise governance of sustainability transitions. Issue 126 (December 2021) - Oliver, Tom H.; Benini, Lorenzo; Borja, Angel; Dupont, Claire; Doherty, Bob; Grodzińska-Jurczak, Małgorzata; Iglesias, Ana; Jordan, Andrew; Kass, Gary; Lung, Tobias; Maguire, Cathy; McGonigle, Dan; et al.
Abstract: The need for sustainability transitions is widely recognised, along with a concurrent need for the evolution of knowledge systems to inform more effective policy action. Although there are many new policy targets relating to net zero emissions and other sustainability challenges, cities, regional and national governments are struggling to rapidly develop transformational policies to achieve them. As academics and practitioners who work at the science-policy interface, we identify specific knowledge and competency needs for governing sustainability transitions related to the interlinked phases of envisioning, implementing and evaluating. In short, coordinated reforms of both policy and knowledge systems are urgently needed to address the speed and scale of sustainability challenges. These include embedding systems thinking literacy, mainstreaming participatory policy making, expanding the capacity to undertake transdisciplinary research, more adaptive governance and continuous organisational learning. These processes must guide further knowledge development, uptake and use as part of an iterative and holistic process. Such deep-seated change in policy-knowledge systems will be disruptive and presents challenges for traditional organisational models of knowledge delivery, but is essential for successful sustainability transformations. Highlights: Knowledge systems are inadequate to deliver transformational policies commensurate with sustainability challenges. Key knowledge types and competences can guide the envisioning, implementation and evaluation of sustainability transitions. Yet these require urgent coordinated reform of the policy system in conjunction with adequate changes in knowledge systems. These reforms include embedding systems thinking literacy and mainstreaming participatory policy making. Also essential is expanding capacity for transdisciplinary research, adaptive governance and organisational learning